Istikhdām Wasā’iṭ al-Biṭāqāt al-Taʿlīmīyah al-Raqamīyah fī Taḥsīn al-Mufradāt ladá al-Ṭullāb fī Madrasah Khayr al-Ummah bi Kutacane - Zahara, Mutia; Nasution, Sahkholid (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2025)
In the field of education, learning media is one of the keys to successful instruction. Flashcards, which can be illustrated cards that help students understand vocabulary, are among the effective tools. This study focuses on improving the vocabulary mastery of eighth-grade students at MTs Khaira Ummah Kutacane, Southeast Aceh, through the use of digital flashcards. The students face difficulties in understanding lessons and communicating due to a lack of Arabic vocabulary. To collect data, this descriptive qualitative research employed observation, interviews, and documentation. The research subjects consisted of one Arabic language teacher and twenty eighth-grade students. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. To ensure the validity of the collected data, method triangulation was applied. This study is expected to provide insight into the effectiveness and efficiency of using flashcard media, particularly in enhancing students' mastery of Arabic vocabulary. في مجال التعليم، تُعَدُّ الوسائط التعليمية أحد مفاتيح نجاح العملية التعليمية. بطاقات تعليمية، وهي بطاقات مصورة تساعد الطلاب على فهم المفردات، تُعتبَر من الأدوات الفعالة. يركّز هذا البحث على تنمية مفردات طلاب الصف الثامن في مدرسة خير الأمة المتوسطة الإسلامية الخاصة كوتاجاني جنوب شرقي اتشيه، من خلال استخدام بطاقات تعليمية الرقمية. يعاني الطلاب من صعوبات في فهم الدروس والتواصل بسبب نقص مفردات اللغة العربية لديهم. ولجمع البيانات، استخدم هذا البحث الوصفي النوعي الملاحظة والمقابلة والتوثيق. وكان معلم اللغة العربية وعشرون طالبًا من الصف الثامن هم عينة البحث. تم تحليل البيانات باستخدام نموذج مايلز وهوبرمان، والذي يشمل عرض البيانات، واستخلاص النتائج، وتقليل البيانات. ولضمان صحة البيانات، أُجري اختبار مصداقية البيانات من خلال منهج التثليث. ويُتوقَّع أن يقدّم هذا البحث صورة واضحة حول فاعلية وكفاءة التعلم باستخدام بطاقات الفلاش، خصوصًا في مجال إتقان مفردات اللغة العربية.